Protease e butirato de sódio nas dietas pré-inicial e inicial de suínos - Silva, Juliana Luis e (2013)
It was aimed to evaluate the zootechnical performance, digestible parameters, diarrhea frequency, blood parameters, organs weight, ph content of the digestive tract and intestinal histomorphology of pigs in the nursery stage fed with feed containing protease and sodium butyrate. In the performance test 80 commercial crossbreed castrated male piglets, 21 days old and initial average weight of 5.11 ± 0.4645 kg, allotted in an experimental lineation randomized block, with four treatments, five repetitions and four animals by repetition. The experiment performance was divided into three phases, being the pre-initial from 5.5 to 9 kg, initial 1 from 9.3 to 15 kg, and initial 2 from 15 to30 kg. Treatments consisted of basal diet, containing 200ppm inclusion of protease, basal diet with 0.3% addition of sodium butyrate and basal diet with protease (200ppm) and sodium butyrate (0.3 %). It was determined the daily weight gain, daily feed intake, nourish conversion, diarrhea frequency; hematological and biochemical profile; pH of the contents of the stomach, duodenum, jejunum, ileum, colon, cecum and rectum; weighing of organs and histomorphometry parameters was determined in the segment of duodenum, jejunum and ileum . The digestibility experiments with pigs from nursery stage has been divided into two stages, with stage I to animals with an average weight of 11.770 ± 0.730 kg and stage II in which animals weighed on average 1.280 kg ± 23,070. In each digestibility experiment, 16 commercial crossbred castrated male piglets were used, the experimental lineation was randomized blocks with four treatments and four repetitions. Treatments consisted of basal diet, basal diet with 200ppp inclusion of protease, basal diet with 0.3% addition of sodium butyrate and basal diet with protease (200ppm) and sodium butyrate (0.3 %). It was determined the digestible energy and coefficient of digestibility and metabolizabilety dry material, gross energy, crude protein and mineral material. Protease and sodium butyrate did not influence the parameters of daily weight gain, daily feed intake and feed conversion. The protease decreases the xii incidence of diarrhea in the initial phase 2. Sodium butyrate and protease isolated and its association improved metabolisability coefficient of the protein, the protease increased mineral absorption. Sodium butyrate decreased the number of blood platelets. There were no differences in pH values of the intestinal contents of the stomach, duodenum, jejunum, ileum, colon, cecum, and rectum. Sodium butyrate showed lower relative weight value of the small intestine and pancreas, protease decreased the weight of the small intestine and the liver, the association of protease and sodium butyrate decreased by the pancreatic weigh. Sodium butyrate increased the base of the duodenal villi protease and villus height decreased in the ileum. The production and enzymatic activity of the protease was not limiting in post weaning performance. The better utilization of nutrients caused by protease and sodium butyrate decreased the functional load of the organs of the digestive tract, reflecting lower weight of the small intestine, liver and pancreas. Sodium butyrate contributes to the development of intestinal mucosa of piglets.